2008
DOI: 10.1097/nmd.0b013e318162aa08
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Neurocognition, Theory of Mind, and Social Functioning in Patients With Schizophrenic Disorders

Abstract: In schizophrenic disorders, impairments in social functioning, neurocognition, and theory of mind (ToM) are frequently reported but little is known about the relationships between them. The aim of this study is twofold: (a) to compare neurocognition, social-functioning, and ToM in patients and controls and (b) to investigate whether impairments in these domains are related to psychiatric symptoms. Participants were 16 outpatients with schizophrenic disorders (DSM-IV), and 16 healthy controls. We administered n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…No association was found for ToM with specifically disorganization symptoms, as has been demonstrated for schizophrenia in meta-analysis (Sprong, et al, 2007), although this may be due to the low level of these symptoms in the CHR patients in our study. Finally, ToM performance was unrelated to the marked social impairment which characterizes this and other CHR cohorts (Ballon, et al, 2007; Cannon, et al, 2008; Corcoran, et al, 2010; Cornblatt, et al, 2007; Shim, et al, 2008; Velthorst, et al, 2009), which might be expected given the finding of lack of association of ToM with social function in patients with schizophrenia (Badan, et al, 2008). The presence of an association of ToM with IQ and not with social function suggests there may be other social cognitive impairments beyond mentalizing which underlie the marked social dysfunction seen in schizophrenia and its risk states.…”
Section: Discussionmentioning
confidence: 61%
“…No association was found for ToM with specifically disorganization symptoms, as has been demonstrated for schizophrenia in meta-analysis (Sprong, et al, 2007), although this may be due to the low level of these symptoms in the CHR patients in our study. Finally, ToM performance was unrelated to the marked social impairment which characterizes this and other CHR cohorts (Ballon, et al, 2007; Cannon, et al, 2008; Corcoran, et al, 2010; Cornblatt, et al, 2007; Shim, et al, 2008; Velthorst, et al, 2009), which might be expected given the finding of lack of association of ToM with social function in patients with schizophrenia (Badan, et al, 2008). The presence of an association of ToM with IQ and not with social function suggests there may be other social cognitive impairments beyond mentalizing which underlie the marked social dysfunction seen in schizophrenia and its risk states.…”
Section: Discussionmentioning
confidence: 61%
“…Accuracy on performance-based ToM tasks is partially dependent on general cognitive skills, such as executive function(40), and can be influenced by state effects, such as attention or effort. Furthermore, while some research shows that poor performance on ToM tasks predicts social functioning(6), other studies show no relationship(41). This suggests that while performance-based measures may assess cognitive capacity for ToM, they do not account for the motivation or success in using these skills to enhance social relationships, which may be better evaluated via self-report and interview-based functional assessments.…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of these factors may direct effective therapeutic interventions, improving treatment outcome. While several studies have suggested that cognitive deficits in schizophrenia may account-at least partially-for patients' impaired social functioning (Addington & Addington, 2000;Green, 1996;Penn, Mueser, Spaulding, et al, 1995), others have failed to establish a robust relationship between neurocognition and social or community functioning in patients with schizophrenia (Bâ, Zanello, Varnier, Koellner, & Merlo, 2008;Bozikas, Kosmidis, Kafantari, et al, 2006;Dickinson & Coursey, 2002). The failure to explain adequately impaired social functioning in light of neurocognitive deficits has led researchers to expand their explorations into the domain of Theory of Mind (ToM) as a potential factor influencing social interactions.…”
Section: Introductionmentioning
confidence: 99%